2003
DOI: 10.1159/000068496
|View full text |Cite
|
Sign up to set email alerts
|

Critical Periods of Eye Development in Vertebrates with Special Reference to Humans

Abstract: This review highlights similarities in human, rodent and avian eye development, focusing on morphogenesis, proliferative activity, apoptosis and mechanistic aspects during the development of the retina, the iris and the cornea. Retinal morphogenesis encompasses four stages: (1) appearance of the ganglion cell layer, (2) formation of the outer plexiform layer separating the inner and outer nuclear layers, (3) formation of immature photoreceptor segments and (4) development of outer photoreceptor segments. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
3
3
0
Order By: Relevance
“…Our findings are in good agreement with recent gene expression studies in the chicken retina, indicating commencement of visual cell differentiation, at around 6 days of incubation (Chen and Cepko, 2002). Early photoreceptor cell morphogenesis in the chicken is thus very similar to that found in other vertebrate species (Lorke and Winking, 1986;Usukura and Obata, 1995;Wu et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are in good agreement with recent gene expression studies in the chicken retina, indicating commencement of visual cell differentiation, at around 6 days of incubation (Chen and Cepko, 2002). Early photoreceptor cell morphogenesis in the chicken is thus very similar to that found in other vertebrate species (Lorke and Winking, 1986;Usukura and Obata, 1995;Wu et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…It is interesting to note that biochemical analyses of chicken retinal lightsensitive pigments indicate that at least four different types of cones exist, each characterized by an opsin with different spectral absorbance (Hart, 2001;Mey and Thanos, 2000). Our observation, that photoreceptor maturation is essentially completed on day 19 of incubation, is consistent with the electrophysiological analyses, showing that the chicken retina becomes light sensitive shortly before the time of hatching (Mey and Thanos, 2000;Wu et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It remains unclear whether the various capacities in differentiation simply reflect different progenitors isolated from different stages of the retinal development [2]. Based on our preliminary data, observations of GFAP immunoreactivity in our cultures using progenitors from fetuses of comparable ages (12 weeks) support the view of such a cellular heterogeneity in progenitor cell isolation from later stages of the retinal development.…”
Section: Discussionsupporting
confidence: 59%
“…The formation of the ganglion cell layer is followed in overlapping phases by the graduate differentiation of horizontal and amacrine cells as well as cone receptors. Towards the end of retinogenesis, rod receptors, bipolar cells and Müller cells are generated, again in an overlapping and yet strictly time-related sequence that is generally conserved across all vertebrate species [1,2]. Cell lineage studies in mammals and amphibian revealed that retinal progenitors are multipotent, and subsets of progenitors can give rise to more than one or two cell types [3].…”
Section: Introductionmentioning
confidence: 99%